Bone Metastases and Bone Loss Medical Treatment in Prostate Cancer Patients - Ferry Safriadi (Acta Medica Indonesiana)
Prostate cancer is a malignancy in urology with the highest incidence metastasize to the bone up to 70%. The incidence of skeletal related event (SRE) by 46.1% such as severe pain, pathologic fractures, spinal compression syndrome and hypercalcemia, with a consequence of higher inpatient care and worsen the patient’s prognosis. Androgen deprivation therapy (ADT) as a metastatic prostate cancer treatment itself causes an osteopenia or osteoporosis. Bisphosphonate inhibits normal and pathologic osteoclast-mediated bone resorption by several mechanisms. Denosumab is the latest treatment option in bone metastases. Multi-study shows the efficacy of denosumab is better than zoledronic acid for SRE prevention. Adverse events between denosumab and bisphosphonate are comparable.